FACTORS ASSOCIATED WITH UTILIZATION OF HEALTH SERVICE TO COMMUNITIES IN THE WORKING AREA OF THE LUBUK PAKAM PUBLIC HEALTH CENTER - Panjaitan, Delita Br; Fadlilah Widyaningsih; Felix Kasim; Kiki Indriani (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Utilization of health care, improved, prevented and cured disease and restored individual or family health in the medical center, where health-care services are performed well, more and more will take advantage of health care, but the opposite may result if the service is felt inadequate. The purpose of this study is to identify the factors associated with the use of health care in the medical center. This type of research is quantitative using a design design for sectionals. The population in this study is the entire community of officers in the human employment area of the central human housing centre 62 people with 33 samples. The instrument used is a questionnaire Data analysis used Chi Square test, univariate analysis and bivariate analysis with a significant level of 5% with an error rate of = 0.05.Analysis shows that there is a relation between an officer 's attitude with a health care user (p value=0.003) < ? 0,005, there is a perception of pain using health care (p value= 0.001) < ? 0.005 and a waiting time relation with health care (p value= 0.003) < ? 0.005. Based on the results of the study, it is suggested that the Lubuk Pakam Health Center is expected to improve the quality of services provided to patients as well as evaluate and pay attention to waiting times to make them even more efficient.